The Correlation between Students’ Autonomy Learning in Watching the English Movies and Their Vocabulary Mastery - Azizah Faridah; Ainul Addinna (Universitas Negeri Padang, 2022)
This study was conducted to determine whether or not students' vocabulary mastery and autonomy learning while watching English movies were related. This study used correlation research as its methodology. The population for this study included second-year students from SMA N 2 Payakumbuh, which had 11 classes. Then, 80 out of 396 students were chosen as the sample for this study utilizing accidental sampling and the Slovin formula. A questionnaire regarding the students' autonomy in learning and a vocabulary test to measure their comprehension of the movies were used as the research's instruments. Following data collection, the correlation was determined using Pearson's Product Moment formula. The results of the data analysis indicated that the 2-tailed significant value was 0.000 less than 0.05, and the correlation results in this study indicated a value of r= 0.997, which was supported by the value of Pearson's product-moment coefficient, which indicated that r>0.05. In this way, the null hypothesis or the first hypothesis was accepted. The study's findings, in general, indicated a correlation between students' mastery of vocabulary and their autonomy in learning while watching English movies. According to the research, students can use media such as English movies to help them learn vocabulary.